Discoursive Adaptation of the Moscow Patriarchate’s Orthodox Diocese in Lithuania (2022–2024) - Bielousova, Gražina; Zaicevas, Deividas (Sociologija. Mintis ir veiksmas, 2025)
The full-scale Russian invasion of Ukraine in February 2022 intensified geopolitical tensions and brought the issue of Orthodox church organizations’ ties to the Moscow Patriarchate to the forefront of the political agenda. The Orthodox Diocese of Vilnius and Lithuania, as part of the Moscow Patriarchate, became a focal point of public debate, facing growing societal distrust and political pressure. The diocese had to navigate between loyalty to Moscow and the need to maintain legitimacy within Lithuanian society. This study examines the discursive practices employed by the diocese to sustain its legitimacy, utilizing critical discourse analysis based on Teun van Dijk’s ‘ideological square’ model. It highlights how the diocese transformed its communication strategies by emphasizing Lithuanian identity, reducing public associations with the Moscow Patriarchate, and presenting itself as a guarantor of peace and stability. Additionally, the research explores how historical narratives, sacralization strategies, and the delegitimization of opposing groups were used to strengthen its position. The study reveals that the diocese strategically modified its communication to mitigate criticism and maintain influence within Lithuanian society. These findings suggest that religious institutions, during times of crisis, actively adjust their discursive practices to safeguard legitimacy and shape public perception.